Stream IMC - how to leverage Sogrape´s wine business in the Uk - communication plan - Ermida, Francisco De Menezes Pena De Azevedo (2022)
The aim of this individual assignment was to determine the best approach for a communications plan to re-launch the Casa Ferreirinha brand in the UK wine market. By targeting the Wine Enthusiast segment and leveraging the story of D. Antónia “Ferreirinha”, and her role as the icon of the Douro valley, Casa Ferreirinha can differentiate itself as the leading brand in the Douro fine wines category. The proposed campaign will use both media and promotional tactics to clarify the brand’s image and reach the goals of increasing product availability and raising the value perception and sales of Portuguese wines in the UK market. Keywords (Sogrape, UK wine market, Communications Plan, IMC, Campaign Proposal)